If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 = 5x + -17 Reorder the terms: 19 = -17 + 5x Solving 19 = -17 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 19 + -5x = -17 + 5x + -5x Combine like terms: 5x + -5x = 0 19 + -5x = -17 + 0 19 + -5x = -17 Add '-19' to each side of the equation. 19 + -19 + -5x = -17 + -19 Combine like terms: 19 + -19 = 0 0 + -5x = -17 + -19 -5x = -17 + -19 Combine like terms: -17 + -19 = -36 -5x = -36 Divide each side by '-5'. x = 7.2 Simplifying x = 7.2
| 9b=54 | | 4x+3=(-1) | | 0=-4x+15 | | 6a=42 | | 5+10x=95+x | | 3X+17=11X-13 | | y-0=8 | | y=.50x+4 | | 3(6+9t)=45t-180 | | 6=3x-6 | | 9f+2f+3f= | | 3t-2(t-1)=5t-4(2+t) | | 15n=45 | | 4b=84 | | 9(x+5)+4(x-3)= | | 5x-14=41 | | 7+6x=2x-9 | | 7(y+8)-3(y+1)= | | 5(b-6)+7b=12 | | x^4+x^2+1=0 | | 64-3x=15x+16 | | 11-8x=43-22x | | 11x-7=9x+3 | | 3x+8=-102-8 | | -55+(-5)+-6=x | | y=6x^2-47x+77 | | .50x+4=-.25x+1 | | -55+(-5)-6=-24 | | 6m-2(7+3m)=(2m-3)-m | | -4-9+(-5)-6=x | | 115-2x=16x+15 | | 0=x-9 |